Substituent-sensitive fluorescence of sequentially N-alkylated tetrabenzotetraaza[8]circulenes - Baryshnikov G. V. Gleb Vladimirovich; Valiev R. R. Rashid Rinatovich; Minaev B. F. Boris Filippovich; Agren H. Hans (2017, 2017)
Title screen